Attitude of motorists towards road ethics: empirical study - Obakemi, Funsho Idowu (Logistics and sustainable transport, 2018)
Road traffic safety among socioeconomic issues has become the major concern across the globe due to rise in road crashes attributed largely to human factor. This study tends to address attitudinal behavior of road users towards road ethics in Ilorin metropolis-Nigeria; covering both driver and motorcyclists and perception of motorists on road traffic enforcement agent. Questionnaire was employed as survey tools. Ordered logistic model were used to analyse the data on attitude of motorists and road traffic laws enforcement agents. About 87% of the 440 administered questionnaire were returned valid. A 3-model analysis was carried out and the findings showed that the attitude of the motorists, road traffic law enforcement agents and demographical index (gender, age and education) correlated with, and influence compliance with road traffic laws.
Keywords: ABC-model; attitude & behavior; etika varnosti v cestnem prometu; odnos in vedenje; ordered logistic model; road safety ethics; urejen logistični model